Post-Yield Deflection of Elastic-Plastic Beams Under Uniformly Increasing Loads - Dorosz, S.; Sawczuk, A.; Biegus, A.; Kowal, Z.; Seidel, W. (Engineering Transactions, 1981)
Experiments on single span and doable span beams beyond the elastic range are reported on in the case when the applied load increases in proportion. The test results are examined in accordance with a deflection analysis based on different approaches. The comparison made allows to state that the finite spread of plastic zones should be accounted for when calculations deflections in the post-elastic mange.